Cadaveric bone marrow mesenchymal stem cells: first experience treating a patient with large severe burns. Issue 1 (18th September 2015) - Mansilla, Eduardo; Marín, Gustavo H.; Berges, Mirta; Scafatti, Silvia; Rivas, Jaime; Núñez, Andrea; Menvielle, Martin; Lamonega, Roberto; Gardiner, Cecilia; Drago, Hugo; Sturla, Flavio; Portas, Mercedes; et al.
Abstract: Background: In January 2005, Rasulov et al. originally published "First experience in the use of bone marrow mesenchymal stem cells (MSCs) for the treatment of a patient with deep skin burns". Here, we present the first ever treated patient with cadaveric bone marrow mesenchymal stem cells (CMSCs) in the history of Medicine. Methods: A young man, who severely burned 60 % of his total body surface with 30 % of full-thickness burns while working with a grass trimmer that exploded, was involved in the study. MSCs were obtained from the bone marrow of a cadaver donor in a routine procurement procedure of CUCAIBA, the Province of Buenos Aires, Argentina, Ministry of Health, Transplantation Agency, cultured, expanded, and applied on the burned surfaces using a fibrin spray after early escharotomy. Results: So far, our preliminary experience and our early results have been very impressive showing an outstanding safety data as well as some impressive good results in the use of CMSCs. Conclusions: Based on all this, we think that improvements in the use of stem cells for burns might be possible in the near future and a lot of time as well as many lives could be saved by many other research teams all over the world. CMSCs will probably be a real scientific opportunity in Regenerative Medicine as well as in Transplantation.